Decreased youth tobacco use in Massachusetts 1996 to 1999: evidence of tobacco control effectiveness. (1st June 2002) - Soldz, S; Clark, T W; Stewart, E; Celebucki, C; Walker, D Klein
Abstract : Objective: To evaluate tobacco control in Massachusetts through examining trends in youth tobacco use from 1996 to 1999. Design: Data are from the 1996 and 1999 Massachusetts Prevalence Study survey of public school students in the state. Participants: Participants consisted of 6800 (1996) and 6980 (1999) students in Massachusetts public school grades 6–12 (approximate ages 11–18 years). Main outcome measures: Outcomes are changes in lifetime and current (past month) cigarette, cigar, and smokeless tobacco. Results: In grades 7–12, there were significant decreases in lifetime (48.3% to 41.9%) and current (30.7% to 23.7%) cigarette use, smokeless tobacco use (lifetime 16.5% to 9.9%; current 4.55 to 2.6%), and current cigar use (12.2% to 8.6%). Decreases occurred for both male and female 7–8th graders. In grades 9–12 decreases were somewhat greater for females than males. Trends for grades 8, 10, and 12 were compared to those seen nationally and in the northeast region in the Monitoring the Future study. For the pooled grades the decreases for cigarettes were greater than those seen nationally or in the northeast region. Conclusions: Results support the effectiveness of the comprehensive Massachusetts Tobacco Control Program. The increasing tobacco rates in the first half of the 1990s have been dramatically reversed. These results suggest that programme efforts should be supported or even expanded in order to decrease further the state's rates of youth tobacco use. The findings suggest that other states may learn useful lessons from Massachusetts' successes.